A CRITICAL ANALYSIS OF RURAL COMMUNITY LEADERSHIP: TOWARDS SYSTEMATISED UNDERSTANDING AND DIALOGUE ACROSS LEADERSHIP DOMAINS - Skerratt, Sarah (The journal of contemporary issues in business and government, 2011)
Key texts in leadership research outline the attributes and practices of the effective leader, consistently emphasising relationship-building, trust, reciprocity, Emotional Intelligence and effectiveness of leadership styles. In rural community development research, there are descriptions of local leaders engendering and sustaining the confidence, resilience and capacity of ‘their’ communities. Such leaders are seen as "champions" working with a cohort of "usual suspects". These arrangements are particularly accentuated and fragile in remoter settlements. With limited exceptions, understanding tends to be largely case-study based. The purpose of this paper, therefore, is to bring together for the first time the "macro" depictions and recommendations for sound leaders and leadership (from key texts) alongside the "micro"-level findings of rural community leadership literature, to review the extent to which the two sets of thinking and evidence resonate and reinforce one another. My analysis shows that: social embeddedness is consistently identified across both literatures, with extra-local links being a focus of the rural literature; Emotional Intelligence and leadership styles are investigated in the leadership literature, but only in one instance in the rural literature; and individual and collective agency and leadership are identified in both literatures. I conclude by identifying the implications of this critical analysis for leadership investment and training: tailored to complexity and embeddedness whilst also operationalising those transferable components of effective individual and group leadership observable in the literature. My findings contribute to understandings that move beyond the "mystique" of rural community leadership towards analyses that are: more systematic; based on an increasing evidence-base across domains; and likely to lead to more robust outcomes in and for remote and rural communities.